Analisis Kompetensi Karyawan Di Hotel Rocky Plaza Padang - Deri Saputra (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
This research aim to to know of interest employee at Rocky Hotel Plaza Padang. This Research represent quantitative descriptive research with approach of kausal asosiatif. The number of sampel in this research was 30 person. The sampling method is purposive sampling. Data collected with enquette with the likert scale.. Result of this research indicate that: (1) employees interest 96,7% respondent reside is in very good category. (2) intellectual interest indicator 83,3% respondent reside is in very good category. (3) emotional indicator 43,3% respondent reside is in good category. (4) social indicator 80% respondent reside is in good category.